Civilians in a world at war, 1914-1918 - Proctor, Tammy M., 1968- (New York University Press, 2010)
World War I heralded a new global era of warfare, consolidating and expanding changes that had been building throughout the previous century, while also instituting new notions of war. The 1914-18 conflict witnessed the first aerial bombing of civilian populations, the first widespread concentration camps for the internment of enemy alien civilians, and an unprecedented use of civilian labor and resources for the war effort. Humanitarian relief programs for civilians became a common feature of modern society, while food became as significant as weaponry in the fight to win. Tammy M. Proctor ar.